2014
DOI: 10.1177/1086296x14552180
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differential Effects of a Family Literacy Program on Language and Literacy Growth of English Language Learners With Varying Vocabularies

Abstract: Many English language learners (ELLs) and children living in poverty begin school with substantially less English vocabulary knowledge than their monolingual, economically advantaged peers. Without effective intervention, these vocabulary gaps are likely to contribute to long-term reading failure. This quasi-experimental study examined the extent to which a family literacy program (FLP) moderated vocabulary development of 158 ELLs (prekindergarten through third grade) from low-income families in relation to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, L2 gains do not have to be at odds with L1 maintenance. Families can be supported in maintaining their L1 through community and educational programs (O’Brien et al, 2014). Additionally, interventions can target and enhance the development of L1 and L2 language and literacy skills in all learners.…”
Section: Societal/contextual Factors Related To L1 and L2 Word Readingmentioning
confidence: 99%
“…However, L2 gains do not have to be at odds with L1 maintenance. Families can be supported in maintaining their L1 through community and educational programs (O’Brien et al, 2014). Additionally, interventions can target and enhance the development of L1 and L2 language and literacy skills in all learners.…”
Section: Societal/contextual Factors Related To L1 and L2 Word Readingmentioning
confidence: 99%
“…Evidence from research has shown parental engagement in children's learning is critical to student success (Fan and Chen, 2001;Desforges and Abouchaar, 2003;Jeynes, 2005Jeynes, , 2007Jeynes, , 2012O' Brien et al, 2014;Purcell-Gates et al, 2014). O' Brien et al (2014) found that children whose parents participated in intervention programmes experienced substantial growth in language and literacy. These findings support the idea that parents are the best partners to close achievement gaps (Goodall, 2017).…”
Section: Literature Review Parental Engagement With Children's Learningmentioning
confidence: 99%